2012
DOI: 10.1002/chem.201103215
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Transfer Reduction of Dinuclear Copper Peroxo and Bis‐μ‐oxo Complexes Leading to the Catalytic Four‐Electron Reduction of Dioxygen to Water

Abstract: The four-electron reduction of dioxygen by decamethylferrocene (Fc*) to water is efficiently catalyzed by a binuclear copper(II) complex (1) and a mononuclear copper(II) complex (2) in the presence of trifluoroacetic acid in acetone at 298 K. Fast electron transfer from Fc* to 1 and 2 affords the corresponding CuI complexes, which react at low temperature (193 K) with dioxygen to afford the η2:η2-peroxo dicopper(II) (3) and bis-μ-oxo dicopper(III) (4) intermediates, respectively. The rate constants for electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 86 publications
2
104
0
Order By: Relevance
“…Another value for comparison is λ = 2.2 eV found for the electron transfer from Me 10 Fc and Me 8 Fc to the peroxo complex [Cu II 2 (N3)(O 2 2− )] 2+ 44 . This very large λ value has its origin in the fact that O–O bond cleavage occurs upon electron-transfer reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Another value for comparison is λ = 2.2 eV found for the electron transfer from Me 10 Fc and Me 8 Fc to the peroxo complex [Cu II 2 (N3)(O 2 2− )] 2+ 44 . This very large λ value has its origin in the fact that O–O bond cleavage occurs upon electron-transfer reduction.…”
Section: Resultsmentioning
confidence: 99%
“…It has, however, been shown that H 2 O 2 can spontaneously decompose, partially or completely, in the presence of ferrocene derivatives. 19 38 and their biomimetic models, is often proposed (and in some cases established) to be an influential factor in their reactivity. In these systems, metalbound thiols can act as proton relay during the catalytic process, but are also capable of tuning the redox potential of the active metal centers.…”
Section: Methodsmentioning
confidence: 99%
“…823 However, selective hydroxylation of benzene to phenol with H 2 O 2 has been difficult because phenol is normally easier to be oxidised to yield over-oxidised products such as p -benzoquinone. 8–21 Although selective hydroxylation of benzene to phenol without over-oxidation has been achieved in some cases, the catalytic mechanism of hydroxylation of benzene to phenol has yet to be clarified, 2430 except for some cases of photocatalytic hydroxylation of benzene to phenol. 2831 Extensive efforts have been devoted to enhance the product selectivity and catalytic activity with heterogeneous catalysts including metal complex catalysts incorporated into a mesoporous material.…”
Section: Introductionmentioning
confidence: 99%